(untitled) (Philological Studies, 2019)
The aim of the study is to determine the predominant models of classification of the conditionals in the Macedonian language as presented in literatute on this topic. The study presents some key concepts related to conditionals and the criteria adopted in the classification of these constructions. A general overview of the considered studies is given, with particular attention to the addressed issues and the extent of coverage of the description of the Macedonian conditional system. The second part of the study deals with the similarities and the differences among the analyzed bipartite and tripartite models and the possible directions of future studies on Macedonian conditionals.